2020
DOI: 10.1108/jmp-06-2019-0360
|View full text |Cite
|
Sign up to set email alerts
|

How control and commitment HR practices influence employee job crafting

Abstract: PurposeBased on the socioemotional selectivity theory, this study aims to explore the differential influences of control and commitment human resource (HR) practices on employee job crafting as well as the mediating role of occupational future time perspective (OFTP).Design/methodology/approachThis study used a two-wave design to survey 53 HR managers and 339 employees of 53 Chinese firms. The hypotheses were tested by conducting multilevel structural equation modeling in Mplus 7.4.FindingsThe results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…This finding suggests that changes in opportunity-enhancing HR practices only lead to changes in job crafting behaviour when older workers experience changes in their psychological empowerment. Although this differs from earlier findings (e.g., Hu et al, 2020;Meijerink et al, 2018;Tuan, 2017) demonstrating a direct positive association between HR practices and job crafting, those studies focused on inter-individual differences, whereas we focus on intra-individual changes. Hence, these previous studies show that employees who are offered more HR practices engage in more job crafting behaviour compared to employees who are offered less HR practices.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…This finding suggests that changes in opportunity-enhancing HR practices only lead to changes in job crafting behaviour when older workers experience changes in their psychological empowerment. Although this differs from earlier findings (e.g., Hu et al, 2020;Meijerink et al, 2018;Tuan, 2017) demonstrating a direct positive association between HR practices and job crafting, those studies focused on inter-individual differences, whereas we focus on intra-individual changes. Hence, these previous studies show that employees who are offered more HR practices engage in more job crafting behaviour compared to employees who are offered less HR practices.…”
Section: Discussioncontrasting
confidence: 71%
“…Although job crafting behaviour is bottom-up and self-initiated behaviour, earlier studies found that organizations can trigger job crafting behaviour, for example, by offering flexibility HR practices (i.e., resource and coordination flexibility; Tuan, 2017;Wright & Snell, 1998) or high-commitment HR practices (Hu et al, 2020;Meijerink et al, 2018). We extend this stream of research and propose that opportunity-enhancing HR practices will stimulate older workers' engagement in job crafting behaviour.…”
Section: Opportunity-enhancing Hr Practices and Job Crafting Behaviourmentioning
confidence: 63%
See 3 more Smart Citations